Anthraquinones from Cratoxylum aborescens (Guttiferae) - Ee, Gwendoline Cheng Lian; Jong, Vivien Yi Mian; Md. Sukari, Mohd Aspollah; Lee, T. K.; Tan, A. (Universiti Putra Malaysia Press, 2010)
Our continuing interest in anthraquinones from the Guttiferae family has led us to look at the genus Cratoxylum. A detailed chemical study on Cratoxylum aborescens resulted in the isolation of three anthraquinones, namely 1,8-dihydroxy-3-methoxy-6-methylanthraquinone (1), vismiaquinone (2) and vismione (3). These compounds were identified using 1D and 2D NMR spectroscopy. This is the first report on the chemistry of Cratoxylum aborescens.